Phylogenetic Analysis of Human Immunodeficiency Virus from People Who Inject Drugs in Indonesia, Ukraine, and Vietnam: HPTN 074. (3rd December 2019) - Sivay, Mariya V; Grabowski, Mary Kathryn; Zhang, Yinfeng; Palumbo, Philip J; Guo, Xu; Piwowar-Manning, Estelle; Hamilton, Erica L; Viet Ha, Tran; Antonyak, Svitlana; Imran, Darma; Go, Vivian; Liulchuk, Maria; et al.
Abstract: Background: HIV Prevention Trials Network (HPTN) 074 evaluated human immunodeficiency virus (HIV) prevention interventions for people who inject drugs (PWID) in Indonesia, Ukraine, and Vietnam. Study interventions included support for HIV infection and substance use treatment. The study enrolled index participants living with HIV and injection partners who were not living with HIV. Seven partners acquired HIV infection during the study (seroconverters). We analyzed the phylogenetic relatedness between HIV strains in the cohort and the multiplicity of infection in seroconverters. Methods: Pol region consensus sequences were used for phylogenetic analysis. Data from next-generation sequencing (NGS, env region) were used to evaluate genetic linkage of HIV from the 7 seroconverters and the corresponding index participants (index-partner pairs), to analyze HIV from index participants in pol sequence clusters, and to analyze multiplicity of HIV infection. Results: Phylogenetic analysis of pol sequences from 445 index participants and 7 seroconverters identified 18 sequence clusters (2 index-partner pairs, 1 partner-partner pair, and 15 index-only groups with 2–7 indexes/cluster). Analysis of NGS data confirmed linkage for the 2 index-partner pairs, the partner-partner pair, and 11 of the 15 index-index clusters. The remaining 5 seroconverters had infections that were not linked to the corresponding enrolled index participant. Three (42.9%) of the 7 seroconverters were infected with more than 1 HIV strain (3–8 strains per person). Conclusions: We identified complex patterns of HIV clustering and linkage among PWID in 3 communities. This should be considered when designing strategies for HIV prevention for PWID. Clinical Trials Registration: NCT02935296. Abstract : In this cohort of people who inject drugs, we observed clusters of genetically related human immunodeficiency virus (HIV) infections. Most seroconverters acquired HIV infection from a source other than their enrolled injection partner living with HIV. Multiple HIV strains were detected in some seroconverters.